At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
So because the factors of the equation are (x-2), (x+3) and (x-3), you set them equal to zero and you get x=2, -3, and 3
(x - 2)(x² - 9) = 0
(x - 2)(x² + 3x - 3x - 9) = 0
(x - 2)(x(x) + x(3) - 3(x) - 3(3)) = 0
(x - 2)(x - 3)(x + 3) = 0
x - 2 = 0 or x - 3 = 0 or x + 3 = 0
+ 2 + 2 + 3 + 3 - 3 - 3
x = 2 x = 3 x = -3
(x - 2)(x² + 3x - 3x - 9) = 0
(x - 2)(x(x) + x(3) - 3(x) - 3(3)) = 0
(x - 2)(x - 3)(x + 3) = 0
x - 2 = 0 or x - 3 = 0 or x + 3 = 0
+ 2 + 2 + 3 + 3 - 3 - 3
x = 2 x = 3 x = -3
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.